Wet and Dry Atmospheric Depositions of Inorganic Nitrogen during Plant Growing Season in the Coastal Zone of Yellow River Delta - Junbao Yu; Kai Ning; Yunzhao Li; Siyao Du; Guangxuan Han; Qinghui Xing; Huifeng Wu; Guangmei Wang; Yongjun Gao (The Scientific World Journal)
The ecological problems caused by dry and wet deposition of atmospheric nitrogen have been widespread concern in the world. In this study, wet and dry atmospheric depositions were monitored in plant growing season in the coastal zone of the Yellow River Delta (YRD) using automatic sampling equipment. The results showed that SO42- and Na+ were the predominant anion and cation, respectively, in both wet and dry atmospheric depositions. The total atmospheric nitrogen deposition was ~2264.24 mg m−2, in which dry atmospheric nitrogen deposition was about 32.02%. The highest values of dry and wet atmospheric nitrogen deposition appeared in May and August, respectively. In the studied area, NO3-–N was the main nitrogen form in dry deposition, while the predominant nitrogen in wet atmospheric deposition was NH4+–N with ~56.51% of total wet atmospheric nitrogen deposition. The average monthly attribution rate of atmospheric deposition of NO3-–N and NH4+–N was ~31.38% and ~20.50% for the contents of NO3-–N and NH4+–N in 0–10 cm soil layer, respectively, suggested that the atmospheric nitrogen was one of main sources for soil nitrogen in coastal zone of the YRD.